A Guide to the New Language of Accounting and Finance. - Hussey, Roger. (Business Expert Press, 2021)
The Guide focuses specifically on the terms used in accounting and finance. Important terms and phrases are identified but with a much longer, in-depth explanation than you would normally find in a dictionary. Not only does each entry gives a thorough explanation of each term, most entries provide two or more references to academic articles that go into much greater depth. Hence, the entries give the reader immediate access to the literature. The Guide also comments on the contribution of the articles which adds to our knowledge. This approach allows the reader to obtain a much deeper level of understanding much more quickly than is available from the usual dictionary.